Microstructure and Glass Phase of Inorganic Binder Coated on Mold for Thin Casting - Eun-Hee Kim (Journal of Nanomaterials, 2012)
A new dual dipping process has been introduced for the increase in the fracture strength of casting mold through the effective glassification of inorganic binder precursors. Two different dipping processes have been employed to investigate the reactivity of the precursors. Process I is that the substrate was coated with a sodium oxide (Na2O) precursor through dipping in the solution, and then a silicon dioxide (SiO2) precursor was coated onto the substrate coated with the Na2O precursor. Process II is the inverse coating sequence for process I. In the case of the mold prepared by process I, the glass phase converted from the precursors is uniformly observed at the surface of the particle and the interface between particles, compared with that by process II, inducing that the fracture strength of the mold prepared by process I is significantly improved. In addition, when the PDMS without a sol-gel reaction was used as the SiO2 precursor, especially in process II, the glass phase is not absolutely observed at the surface of the particle owing to the evaporation of PDMS and Na ion during the heat treatment, resulting in the collapse of the mold sample after the heat treatment.